(untitled) (Nóema, 2012)
In order to outline the relationship between Ethics and Aesthetics of architecture and answering the main question «what is/ought to be a good architect?», the essay discusses the Wittgenstein’s thesis by which «the work of art is the object seen sub specie aeternitatis; and the good life is the world seen sub specie aeternitatis. This is the connexion between art and ethics».